The Saudi thoracic society guidelines for vaccinations in adult patients with chronic respiratory diseases - Mohammed Al Ghobain; Fayssal Farahat; Mohammed Zeitouni; Waleed Alsowayan; Sultan Al-Awfi; Ali AlBarrak; Shareefah Al-Basheri; Fatmah Alhabeeb; Esam H. Alhamad (Annals of Thoracic Medicine)
Adult patients with chronic respiratory diseases (CRDs) are considered high risk group who are more likely to experience worse clinical outcomes if they acquire viral or bacterial infections. Vaccination is the best preventive tool to reduce the risk of infection and disease occurrence and to reduce the level of severity of complications associated with the various vaccine-preventable infections. These guidelines were developed by the Saudi Thoracic Society task force to emphasize the critical importance of improving the vaccine coverage rates in adult patients with CRD. They are intended to serve as a reference for healthcare practitioners managing CRD patients. The guidelines aimed to review the current knowledge related to vaccination efficacy in adult patients with CRD, based on the recent evidence and recommendations. Integrating the administration of the recommended vaccines in routine healthcare, such as during outpatient visits or before hospital discharge, is crucial for improving the vaccination rates in high-risk patients. The key strategies to address this public health priority include simplifying vaccination guidelines to enhance their accessibility and implementation by healthcare providers, increasing awareness in both the patients and healthcare providers that vaccines are not only intended for children. Additional strategies include maintaining continuous surveillance and advance research to discover novel vaccines. This approach aims to expand the range of preventable diseases and improve overall health and well-being. Vaccine hesitancy remains a significant challenge that necessitates a clear understanding of the community concerns. Providing appropriate education and communication, as well as addressing these concerns, are the crucial steps toward improving vaccine acceptance and uptake. By implementing these guidelines and multifaceted strategies, healthcare systems can optimize vaccine coverage and protection for patients with CRD, reduce the burden of vaccine-preventable complications, and improve the clinical outcomes in this vulnerable population.